PENINGKATAN KESADARAN SISWA SD NEGERI 5 KEDERI MELALUI AKTIFITAS PEMILAHAN SAMPAH ORGANIK, ANORGANIK, DAN RESIDU - ni putu gita darmayanti; I Ketut Arya Krisna Ananta Wijaya; Ni Komang Dian Yuliasih; I Gede Komang Bagus Dana Swara; Ni Wayan Restiani; I Ketut Windu Mahadika; Ni Made Yutina; I Kadek Wahyu Arianda; I Komang Supriyanata; Ekarista Sanur; Marselina Mamohungu; Vinsensiana Riani; Marianto Rengge (Sewagati, 2026)
The waste problem remains an environmental issue in elementary schools, including Kederi 5 Public Elementary School, due to students' lack of understanding regarding waste sorting. This community service activity aims to increase students' awareness through education on sorting organic, inorganic, and residual waste. The implementation methods included interactive socialization, practical sorting demonstrations, and mentoring. The program's success was evaluated directly through behavioral observations of students' waste disposal habits at school. The results showed a positive behavioral shift, with students becoming accustomed to sorting and disposing of waste into the appropriate bins. This activity successfully stimulated pro-environmental behavior, which is expected to continue through school supervision.